Hepatotoksičnost zdravilnih rastlin in prehranskih dopolnil - Šetina, Andrea (Farmacevtski vestnik, 2019)
The use of medicinal plants is rising globally. Consumers are becoming more aware of the consequences of leading an unhealthy lifestyle, therefore the interest in supposedly natural products is not surprising. medicinal plants come from nature, which is why people perceive them as safe. Plants that are acutely toxic have long been recognized by humans as harmful and not used. However, plants that are chronically toxic are more difficult to recognize as harmful, and are continued to be used. On the contrary, several studies confirm hepatotoxicity of common herbs that could possibly lead to life-threatening liver failure. Buying these products online can be utterly dangerous due to the lack of control, toxic ingredients and potential presence of heavy metals. In this article, we will present the mechanisms of hepatotoxicity of medicinal plants and show some medicinal plants that can be hepatotoxic when used incorrectly.
Keywords: hepatotoksičnost; okvara jeter; prehranska dopolnila; Zdravilne rastline